Study on the Work Life Balance of Hotel Employees in Metro Cities - Mr. Paresh Bali, Dr. Manohar Sajnani, Dr. R. K. Gupta (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Aim: The aim of study is to find out the levels of work life balance (WLB) experienced by hotel employees in metro cities and ascertain factors that influence WLB. Materials and Methods: the study is based on, analysis of information collected from 732-hotel employee working in hotels of metro cities of India. With the help of MS Excel and SPSS the data was organized and analysed through statistical tests like factor analysis, correlation analysis, Student t test, ANOVA and Tukey HSD to interpret the results. Results and discussions: The study found that the levels of WLB experienced by hotel employees in metro cities present a high variation depending on organizational factor, gender, age group and family structure. Overall, there is a lack of satisfactory WLB for the employee of hotel industry. Conclusions: There is a lack of WLB experienced by hotel employees in metro cities, employees working in front of the house operations and housekeeping experience higher levels of WLB. The levels of WLB experienced by an employee, with age, follows a U shape curve. Factors like family structure and gender also influence levels of WLB.